ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PERMINTAAN KARET ALAM DI INDONESIA - Haryanto, Haryanto; Sunariyo, Sunariyo; Abdul Mukti (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2019)
The research is aimed to know factor affect rubber and demand in Indonesia. This research is used time series period from 1989 until 2016. The analyze used econometric model in the form of simultaneous aquations with Two Stage Least Square Method and helped Statistical Analyze System consisting. Its divided into two block (Production and Demand block) where every block consisting two structural aquations. Result showed that production block, natural rubber production response (QKR) is affected by area of rubber produces (AKR), price of domestic natural rubber (HKR), price of export natural rubber (HXKR) and Indonesia natural rubber demand (DKR) with each affect of 0,2926, 0,0480, 0,0222, and 0,8841. Price response of domestic natural rubber (HKR) is affected by price of world natural rubber (HKRD), export of natural rubber (XKR) and the rupiah against the dollar of USA (ER) with each affect of 0,2112; 2.4562 and 571,6580). It’s demand block, response of Indonesia natural rubber demand (DKR) is affected by price of domestic natural rubber (HKR) and number of vehicles (JKB) with each affect of -0,0176 and 0,0082. Before response of export of nutural rubber (XKR) affects price of domestic natural rubber (HKR). Its affected by production of Indonesia natural rubber (QKR), price of export of natural rubber (HXKR) and the rupiah against the dollar of USA (ER) with each affect of 0,2664; 0,0238 and 26,8898.